The COVID-19 Pandemic and The Global Financial Crisis - A Comparison of Symptoms in The Visegrad Group - Zbigniew STANIEK; Arkadiusz J. DERKACZ; Agnieszka DUDZIAK; Bartosz SPYCHALSKI (Communications of International Proceedings, 2021)
The research concerns the issues of the global financial crisis of 2009 and the crisis caused by the COVID-19 pandemic of 2020. They were conducted on the economies of the Visegrad Group countries in the period 2000-2020. The first aim of the research was to try to identify the symptoms of economic crises. The second goal, however, was to attempt a comparative analysis of the relative changes of 7 indicators for two economic crises. The analysis used indicators that were considered indicators of symptoms of economic crises. This was to lead to an answer to the main research question: what were the differences in the symptoms of the crises of 2009 and 2020? The research used a comparative analysis based on the agglomeration method. Euclidean distances were used when formatting the clusters. The squared values for relative changes in particular quarters of 2009 and 2020 in relation to the standard deviation in the period 2000-2020 were calculated. The presented research results allowed to draw two key conclusions. They boiled down to the fact that the COVID-19 pandemic triggered a smaller economic slowdown than the global financial crisis. Additionally, this slowdown was short-term and occurred mainly in Q2 2020.
Keywords: economic crisis; COVID-19 pandemic; economy